Advanced characterization and resistance to failure of novel electron beam physical vapour deposited thermal barrier coatings for net zero - an experimental study - Almandoz Forcen, Koldo (Cranfield University, 2024)
The efficiency of aeroengines is of paramount importance to reduce the environmental impact and operating costs of the aviation industry. The attainable efficiency gains are limited by the durability of the components in the hot section of the engine, the turbine. Thermal Barrier Coatings (TBCs) are ceramic layers protecting the metallic components in the hot section of the engine. Improvements to the thermal capability of these coatings translates to overall efficiency gains. However, achieving them is a steep challenge, due to the harsh environment in which TBCs operate. Overcoming this challenge requires a deep understanding of the links between manufacturing process, resulting microstructure and behaviour of TBCs, as well as their failure modes. Electron Beam Physical Vapour Deposition (EB-PVD) was used to deposit TBCs with a range of microstructures. Their microstructural features were quantified through a method developed to that end. This analysis was complemented through the advanced crystallographic study of the TBCs using Electron Back Scattered Diffraction (EBSD). The characterized systems were tested for life-limiting failure modes: CMAS1 attack, erosion and cyclic oxidation. The response of the TBCs to CMAS infiltration and the effect of the microstructural features was studied. A method for the quantification of CMAS infiltration depth was developed and validated using isothermal and thermal gradient exposures. This method allowed for identifying of a previously unreported two-stage mechanism for CMAS infiltration in EB-PVD TBCs. The erosion resistance of the produced coatings was investigated through high velocity particle impact testing. The morphology of damage was observed and material loss 1 after its constituents, Calcia, Magnesia, Alumina, Silica iimechanisms were proposed based on the microstructural and crystalline characteristics of each coating. The proposed methods will help accelerate the development of novel TBCs by laying the foundations for a mechanistic understanding of coating characteristics and their effect on failure behaviour.
Schiller, Tara - Associate Supervisor Nicholls, John R. - Associate Supervisor
Keywords: 7YSZ; Yttria Stabilized Zirconia; Gadolinium Zirconate; GZO; CMAS; Erosion; Cyclic oxidation; Image analysis; Infiltration